(untitled) (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2026)
Gynura procumbens has the potential to serve as forage for ruminant livestock. This study aimed to evaluate the growth parameters and biomass of G. procumbens cultivated on latosol soil under varying levels of urea fertilization. The experimental design employed a Complete Block Design (CBD) based on four levels of urea application with ten replicates. The treatments included: P0 as control (compost (8 ton ha-1) + NPK 15-15-15 (200 kg ha-1), P1 = P0 plus 100 kg ha-1 urea (4.6 g plant-1), P2 = P0 plus 200 kg ha-1 urea (9.2 g plant-1), and P3 = P0 plus 300 kg/ha urea (13.9 g plant-1). Observed parameters included plant height, number of stems and leaves, fresh and dry biomass, and nutrient content. Data were analyzed using ANOVA, followed by Duncan’s multiple range test for significant differences. Results indicated that increasing urea levels reduced the number of branches and leaves, as well as the fresh and dry weight of leaves and stems. Urea application did not significantly affect plant height, shoot and leaf area, shoot fresh weight, or leaf nutrient content. The study concluded that G. procumbens does not require additional urea fertilizer when grown on latosol soil.